Paradoxes in the Strategic Choices of Companies in the Furniture Industry in Poland - Glińska-Neweś, Aldona; Sopińska, Agnieszka; Escher, Iwona; Józefowicz, Barbara; Łuka, Alicja (Studia Oeconomica Posnaniensia, 2019)
In recent years, the perception of the essence of strategic decisions in companies has evolved towards the need for reconciling diverse paradoxes by decision-makers. Managers are no longer expected to have unambiguous, either or choices. They are expected to make decisions within a space generated by seemingly opposite goals, approaches or procedures. Reconciling paradoxes brings better results to a company than a traditional approach, due to releasing the potential of creative solutions based on the innovative synergies of options that were considered to be in conflict. The aim of the paper is to identify paradoxes occurring in strategic choices undertaken by companies in the furniture industry in Poland. The empirical study was purposely conducted in one sector; therefore many conditions of the decision-making process could be treated as homogeneous. The study with the use of the CATI method was carried out in the time period of March - September 2018. The measurement scale was proposed and grounded in de Wit and Meyer's concept of strategic paradoxes (2007). Based on the responses from 201 companies, it was found that decision-makers in the Polish furniture industry reconcile primarily contradictions related to strategy formation and external co-operation.